Relacionamento fraterno feminino e vida profissional: um estudo de caso - Machado, Raíssa Ducatti Lino (2013)
The objective of this study was to comprehend the construction and reconstruction of women´s sibling relationship between sisters of medium to high income living in urban areas who have an active professional life. We intended to understand the reciprocal influences between these women throughout their lives and the implications of such influences on their professional lives. To achieve this objective we performed a case study. Open interviews were conducted with four sisters whose narratives allowed us to better understand their life experiences, current and past. We have found that the bonds between them are built based on loyalty and mutual support which becomes evident throughout their relationships histories and influences important themes in all of their individual lives, among which is their professional life